(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
In our country, the increase in the production of wastes has posed a great challenge for humanity. India is the leading producer of waste rubber and if any kind of method that makes it possible for us to reduce the ill effects of it on the environment and human life is to make use of it in the best possible way. Waste rubber, being a non biodegradable material has found a better place in case of embedding useful and effective properties in bitumen thus enhancing the performance of bituminous concrete. So researchers found its use in the case of bitumen and in this paper we would be analyzing the performance and behavior of bitumen modified with rubber. Some of the main features of road pavement construction would be studied; such features are: - stability, stiffness, fatigue, resistance, rutting and so on.